2014
DOI: 10.1007/s40615-014-0030-6
|View full text |Cite
|
Sign up to set email alerts
|

Minority Underrepresentation in Academia: Factors Impacting Careers of Surgery Residents

Abstract: Background Underrepresentation of minorities within academic surgery is an ever present problem with a profound impact on healthcare. The factors influencing surgery residents to pursue an academic career have yet to be formally investigated. We sought to elucidate these factors, with a focus on minority status. Methods A web-based questionnaire was sent to all administered to all ACGME-accredited general surgery programs in the United States. The main outcome was the decision to pursue a fully academic vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 21 publications
(26 reference statements)
0
23
0
Order By: Relevance
“…Furthermore, educational debt over $150,000 among general surgeons has been associated with choosing a nonacademic career. 16 From the same 2009 study, Kibbe and coworkers 4 found that 29.3% of surgeon respondents had considered pursuing a nonacademic career because of their educational debt, and 29.5% felt that their educational debt burden affected their academic productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, educational debt over $150,000 among general surgeons has been associated with choosing a nonacademic career. 16 From the same 2009 study, Kibbe and coworkers 4 found that 29.3% of surgeon respondents had considered pursuing a nonacademic career because of their educational debt, and 29.5% felt that their educational debt burden affected their academic productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding regarding a negative association between debt and academic-medicine career aligns with results of a national general surgery resident survey, which reported that high debt (>$150,000) among senior residents was associated with a lower likelihood of academic-medicine career plans. 23 Our findings underscore the importance of promoting awareness about NIH Loan Repayment Programs among highly indebted general surgery residents who might otherwise consider pursuing research-related careers. 41 Our study has several strengths.…”
Section: Discussionmentioning
confidence: 59%
“…Our findings extend previous single institutional findings of general surgery training-program graduates' career paths [2][3][4] and a national survey of general surgery residents' career intentions. 23 That graduation year was negatively associated with faculty appointment in our sample was not unexpected as faculty appointees continue to accrue among US medical school graduates for 15 years after graduation. 33 We have not yet followed the surgeons in our study beyond initial faculty appointment to determine if GME-research participation is associated with a greater likelihood of academic-medicine retention and promotion, which will be additional long-term indicators of success as academicians, beyond initial appointment.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Diversity in medicine and surgery is important as it leads to more inclusive and patient-centred care, increased patient compliance, satisfaction and participation in clinical trials, and greater access to care for disenfranchised communities [ 4 ]. There remains a lack of representation of minority groups in positions of leadership in surgery [ 5 ], and mentorship is a crucial factor in promoting a career in surgery [ 6 10 ]. Roberts SE et al found that the perceived barriers preventing African Americans from pursuing a career in surgery included ‘lack of mentorship’, ‘difficulty finding minority role models’, and ‘fighting stereotypes’ [ 11 ].…”
mentioning
confidence: 99%